2014
DOI: 10.1159/000366422
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Rehabilitation in Patients with Rotator Cuff Calcific Tendinopathy after Ultrasound-Guided Percutaneous Treatment

Abstract: Objective: To evaluate the efficacy of a specific rehabilitation program for patients in whom ultrasound-guided percutaneous treatment (UGPT) was performed for rotator cuff calcific tendinopathy (RCCT). Subjects and Methods: In this prospective observational study, 86 patients (22 males and 64 females) with shoulder calcific tendinopathy treated with UGPT were enrolled. At the end of the procedure, a corticosteroid injection into the subacromial-subdeltoid bursa was performed. The patients were then asked to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The cause of calcific tendonitis is not known 8 ) but studies related to conservative, noninvasive, and non-surgical interventions used to treat calcific tendonitis have proved that the absorption of calcific tendonitis occurs naturally 5 , 8 , 9 , 10 ) . Several conservative interventions for the decalcification of calcific tendonitis, pain relief, and the improvement of joint function of the area affected by calcific tendonitis have been noted, but physiotherapies to treatment these symptoms, such as manual therapy and therapeutic exercises, have only been performed in combination with other conservative interventions 8 , 9 ) , Finding cases that applied independent, aggressive, and intensive physiotherapy for the treatment of calcific tendonitis is difficult. Thus, this study intended to identify the effects of intensive and independent PNF exercise on calcific tendonitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cause of calcific tendonitis is not known 8 ) but studies related to conservative, noninvasive, and non-surgical interventions used to treat calcific tendonitis have proved that the absorption of calcific tendonitis occurs naturally 5 , 8 , 9 , 10 ) . Several conservative interventions for the decalcification of calcific tendonitis, pain relief, and the improvement of joint function of the area affected by calcific tendonitis have been noted, but physiotherapies to treatment these symptoms, such as manual therapy and therapeutic exercises, have only been performed in combination with other conservative interventions 8 , 9 ) , Finding cases that applied independent, aggressive, and intensive physiotherapy for the treatment of calcific tendonitis is difficult. Thus, this study intended to identify the effects of intensive and independent PNF exercise on calcific tendonitis.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the patient’s calcification decreased by about 86% from 135.7 mm 2 to 19.2 mm 2 , and the subject’s VAS, SST, CMS, and PROM results improved in accordance with this decrease. Abate et al 9 ) reported there was a greater effect on the VAS and CMS scores of patients with calcific tendonitis of the rotator cuff in a group in which intervention with exercise was applied after ultrasound-guided percutaneous treatment (UGPT) than in a group in which passive exercise was applied with UGPT was applied. These results corresponded with the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Following a specific rehabilitation protocol after the procedure may also result in better outcomes. [26][27][28] Ultrasound-guided needling also showed better results in function restoration and pain relief in the short term than extracorporeal shock wave therapy, both improving clinical outcome and eliminating calcific deposit. 29 The correct selection of patients to be submitted to ultrasoundguided percutaneous treatment is crucial.…”
mentioning
confidence: 94%